1990
DOI: 10.1017/s0022112090002361
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady three-dimensional natural convection in a fluid-saturated porous medium

Abstract: Natural convection in a cube of fluid-saturated porous medium having a constant temperature top and bottom is studied numerically. In the first of two special cases considered, the vertical sides are insulated. In this case, the numerical simulations indicate permanently unsteady regularly and irregularly fluctuating convective states at Rayleigh numbers (R*) above 550. The regularly fluctuating convective state defined by simply periodic oscillations in the Nusselt number begins at R* between 550 and 560. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Schubert & Straus (1979) found that the steady cubic‐cell flow is replaced by a time‐dependent oscillatory regime at high Rayleigh numbers. Improving the numerical accuracy of the computations, Kimura et al (1989), Stamps et al (1990) and Graham & Steen (1991) located the transition of the [111] mode from the steady to the oscillatory state at R = 580.…”
Section: Introductionmentioning
confidence: 99%
“…Schubert & Straus (1979) found that the steady cubic‐cell flow is replaced by a time‐dependent oscillatory regime at high Rayleigh numbers. Improving the numerical accuracy of the computations, Kimura et al (1989), Stamps et al (1990) and Graham & Steen (1991) located the transition of the [111] mode from the steady to the oscillatory state at R = 580.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the S3 mode was found to undergo a bifurcation to either S7 or S10 depending on the perturbation given by the time-step value chosen in the simulation when Ra * is increased from 600 to 610. Straus & Schubert 1978, 1981Horne 1979;Steen 1983;Kimura et al 1989;Stamps et al 1990;Graham & Steen 1991 Table 2. Flow structures, their range of existence and structures reached after bifurcation.…”
Section: Effect Of Rayleigh Numbermentioning
confidence: 99%
“…Both studies report that the flow pattern becomes less symmetric prior to the onset of time dependence. Stamps, Arpaci & Clark (1990) found that regularly fluctuating convection begins at Ra * between 550 and 560 from steady three-dimensional flow.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of transient natural convection in porous media has appeared frequently in the literature for two-dimensional situations, while for threedimensional problems it has been much more rare, especially for fully transient situations, mainly due to the sometimes prohibitive increase in computational effort associated with the most usual purely discrete solution approaches. Some relevant contributions to the present analysis, in dealing with two and threedimensional natural convection within porous cavities, are listed below [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%